PROFESSIONAL DEVELOPMENT OF PRE-SERVICE TEACHERS IN AN ENGLISH LANGUAGE TEACHER EDUCATION PROGRAM - Betül Bal-Gezegin; Gözde Balıkçı; Fatma Gümüşok (International Online Journal of Education and Teaching, 2019)
This case study aims to explore the professional development experiences of two fourth–year student teachers (mentees, hereafter) and their two cooperative school teachers (mentors, hereafter) in the practicum component of English language teacher education program in a state university. The participants of this study have been doing their internship in their last year of pre- service education.  In order to understand the mentorship process in terms of professional development practice for those involved, two mentees and their mentors were interviewed. The results indicated that the relationship between mentor and mentee is a continuous, dynamic, and fruitful for both parties. Mentees reported that they developed a teacher identity and improved themselves in particularly classroom management although their mentors are not the ideal teachers. On the other hand, mentors reported that they feel refreshed and update their knowledge with the help of mentees. Implications for the mentorship and practicum process will be discussed.